The water quality of the River Dun and the Kennet and Avon Canal - Neal, Colin; House, W. Alan; Jarvie, Helen P.; Neal, Margaret; Hill, Linda; Wickham, Heather (Journal of hydrology (Amsterdam), 2006)
The water quality of the River Dun and associated surface waters (a reservoir, two tributaries of the Dun, the Kennet and Avon Canal and the River Kennet to which the Dun drains) is described for a wide range of major, minor and trace elements. The water quality is determined by inputs from: (a) geologic sources (Ca, Sr concentrations and alkalinity) and (b) contaminant inputs from farming and sewage (Na, Cl, B, soluble reactive phosphorus and nitrate). As river water is mainly supplied from the Chalk aquifer and riparian areas, the water quality variation is damped, but there are occasional storms, where near surface/surface runoff delivers higher nutrient and suspended sediment concentrations, but dilutes determinands derived predominantly from geologic and point sources. River and canal water quality is also modified by in-stream biological processes in spring and summer, which remove nutrients (N, P and Si) and CO 2 from the water, bringing about precipitation of calcium carbonate and thus reductions in Ca concentrations and alkalinity. The biological effects are particularly marked for the Kennet and Avon Canal. The River Dun and Kennet and Avon Canal have been subject to episodic fish-kills and concern has been expressed about the role of event-based resuspension of bed sediments and mobilisation of dredged sediments on dissolved oxygen levels within the river. Therefore, fluvarium experiments on sediment–water interactions were undertaken to examine the potential effects of bed sediment disturbance on dissolved oxygen levels. The results of the fluvarium experiments demonstrate an ecologically-significant 30% reduction in dissolved oxygen levels following bed sediment disturbance. This reduction in DO concentrations was greater than expected from calculations using the measured sediment-oxygen demand. However, it is not clear that the bed sediments are mobilized to sufficient extent in the field for deleterious loss of DO. Indeed, much of the resuspended sediments within the canal and the river may well come from runoff from the land. The results also demonstrate key hydrogeochemical processes in Chalk-fed surface waters, with implications for environmental management.